Exploring local idioms of distress among Sudanese youth who witnessed the sit-in massacre: developing the Khartoum distress scale - Badri, Abdelrahman Elmahadi Gasim (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.